Correção de fósforo do solo no sistema de cultivo milho - aveia-branca - soja, em genótipos com eficiência nutricional contrastante - Manica, Jonas (2021)
Among the factors that influence the effect of phosphate fertilization on grain crops, the residual effect of this fertilization on cropping systems, and how this is influenced by the nutritional efficiency of phosphorus (P) of the genotypes, is still poorly understood. The objective of this research was to evaluate the residual effect of phosphate fertilization in the corn-oat-white soybean crop system, comparing two soil P correction strategies: fertilizer application in the corn sowing line (Strategy 1) and application in the white oat sowing line (Strategy 2), in genotypes with nutritional efficiency to contrasting P. The experiment was carried out in the field, in a Humic Dystrophic Red Latosol, under no-tillage, in Passo Fundo, RS, with corn, white oat and soybean crops. The experimental design was in randomized blocks in a factorial scheme (2 P correction strategies) × 2 genotypes x 7 P doses), with four replications. Correction doses of P were: 0; 30; 60; 90; 120; 150; 190 kg P2O5/ha. In addition to these doses, 60 kg P2O5/ha was applied as maintenance fertilization. The following were evaluated for each crop and crop system: grain yield (GR), net income, calibration of soil P content. The GR differed between the genotypes, except for the corn hybrids. The GR of the most efficient cultivar of white oat (URS Taura) was about 17% higher than that of UPFPS Farroupilha, resulting in higher net income with the dose of 60 and 90 kg P2O5/ha. Soybean GR was about 23% higher in the BMX Ativa cultivar (more efficient cultivar) in relation to DM53i54 (less efficient cultivar), resulting in higher net income under the residual effect of the dose of 210 kg P2O5/ha; and the inefficient cultivar under the residual effect of doses of 150 (Strategy 1) and 250 kg P2O5/ha (Strategy 2). The GR of the corn oat-white-soybean system, obtained with the efficient genotypes, was higher with the doses of 210 kg P2O5/ha (Strategies 1 or 2). /there is. The critical levels of P levels in the rhizospheric soil, for the phosphate fertilization of the corn-oat-white-soybean system, were 40 and 20 mg P/kg (Strategy 1) and 13 and 16 mg P/kg (Strategy 2 for the efficient and inefficient genotypes, respectively. It is concluded that the grain yield obtained in the corn-oat-soybean system is not influenced by the P correction strategies, but varies with the P doses and the nutritional efficiency to phosphorus (P) of the genotypes tested. The classes of interpretation of P levels in the soil suggested by the research should be adapted for use in the corn-oat-white-soybean system, in which phosphate fertilization is performed only on corn and white oat. The choice of nutritionally efficient genetic material enhances grain yield, with less demand for P application.